The Spirit of romanticism [videorecording] - Barnes, John (Encyclopedia Britannica Educational Corporation [producer], 1977)
Outlines the historical events and cultural influences of the Romantic age, using vignettes which highlights the causes of such figure as Jean Jacques Rosseau ; Napoleon Bonaparte, Carlyle, Wordsworth, Sheley, Byron, Beethoven, Delacroix, and Chopin.